2018
DOI: 10.1111/jicd.12374
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of radiation‐protection knowledge, attitudes, and practices of North Queensland dentists

Abstract: Aim Queensland has current radiation‐protection guidelines; however, with the absence of data exploring compliance and implementation, the efficacy is unknown. The aim of the present study was to investigate the knowledge and attitudes on radiation protection among private North Queensland (NQ) dentists. Methods A quantitative methodology was employed in an observational and descriptive study using questionnaires for data collection. Results Of the 154 questionnaires distributed, 63 were completed and returned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 14 publications
2
14
0
4
Order By: Relevance
“…Positive attitude Development about radiation protection leads to motivation for enhancing the knowledge; hence, more proper practice. Developing a positive attitude is time-consuming, and mostly occurs over the long run and based on experience [18]. Regarding performance, most studies revealed an average performance of HCWs concerning radiation protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive attitude Development about radiation protection leads to motivation for enhancing the knowledge; hence, more proper practice. Developing a positive attitude is time-consuming, and mostly occurs over the long run and based on experience [18]. Regarding performance, most studies revealed an average performance of HCWs concerning radiation protection.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests different results about the level of awareness, attitude, and performance of healthcare workers about radiation protection across different countries [14][15][16]. Further, many studies have shown that HCWs with good knowledge may lack a good attitude about radiation protection [17][18][19]. Also, many individual studies have found poor knowledge about radiation protection [14,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…We found that a majority of pediatric dentists in Serbia would not expose women to any kind of radiography. A research of North Queensland dentists 7 had an opposite result. The most preferred procedural change for pregnant patients was to take only intraoral radiographs if urgent for diagnosis (95.2%).…”
Section: Indications For Radiographymentioning
confidence: 96%
“…Basic knowledge about the age of their x-ray units, cone and colimator types, kilovolts and milliamperes was porely shown in our research, with the prevalence of dentists that did not have answers to these questions. Knowledge, attitudes and practices of North Queensland dentists 7 shows that most radiographic equipment appeard to be greater than 6 years old. In approximately two thirds of cases (61.3%), the dentists used tube voltage of 65-70kVp, and half of the responders a tube current of under 10mA.…”
mentioning
confidence: 99%
“…20 menganggap bahwa gonad adalah organ yang paling penting untuk dilindungi dari paparan radiasi. 35 Celemek timbal banyak digunakan oleh dokter gigi karena dianggap dapat mereduksi dosis efektif dengan cara melindungi abdomen dan gonad dari paparan radiasi hambur. Pemakaian celemek timbal memiliki relevansi klinis yang kecil dalam usaha perlindungan paparan radiasi pada radiografi kedokteran gigi karena paparan radiasi hambur yang mencapai organ gonad sangat rendah sehingga kontribusinya sangat rendah terhadap dosis efektif total pasca pemeriksaan radiografi kedokteran gigi.…”
Section: Persepsi Dokter Gigi Terhadap Penggunaan Pelindung Tiroidunclassified